Beatification of Cardinal Henry Newman. (December 2017) - May, Peter
Claims of a miracle cure require objective and thorough investigation with a review of all contemporaneous medical records. This paper describes instances of apparent miraculous recoveries from fatal or incurable illnesses. Following more rigorous review of the medical documentation, when available, a different story emerges. Misdiagnosis and/or appropriate treatment account for the best cases.